The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1145/3158230
|View full text |Cite
|
Sign up to set email alerts
|

Observation-Level and Parametric Interaction for High-Dimensional Data Analysis

Abstract: Exploring high-dimensional data is challenging. Dimension reduction algorithms, such as weighted multidimensional scaling, support data exploration by projecting datasets to two dimensions for visualization. These projections can be explored through parametric interaction, tweaking underlying parameterizations, and observation-level interaction, directly interacting with the points within the projection. In this article, we present the results of a controlled usability study determining the differences, advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 60 publications
(60 reference statements)
2
33
0
Order By: Relevance
“…The concept of different interaction stages is not limited to clustering, of course. Our structure of this dimension matches quite well with the types of interaction identified by Self et al [87]. They distinguish "Parametric interaction" and "Observation-level interaction," with the former referring to users directly specifying or modifying design parameters of an algorithm, and the latter allowing users to interact with individual data items, usually in an interactive graphical tool.…”
Section: At Which Stage Is the Interaction Happeningsupporting
confidence: 81%
See 1 more Smart Citation
“…The concept of different interaction stages is not limited to clustering, of course. Our structure of this dimension matches quite well with the types of interaction identified by Self et al [87]. They distinguish "Parametric interaction" and "Observation-level interaction," with the former referring to users directly specifying or modifying design parameters of an algorithm, and the latter allowing users to interact with individual data items, usually in an interactive graphical tool.…”
Section: At Which Stage Is the Interaction Happeningsupporting
confidence: 81%
“…They distinguish "Parametric interaction" and "Observation-level interaction," with the former referring to users directly specifying or modifying design parameters of an algorithm, and the latter allowing users to interact with individual data items, usually in an interactive graphical tool. Self et al [87] argue that these two forms of interaction offer distinct and complementary capabilities, and are likely to lead to different types of insights. Parametric interaction offers high degree of control but requires deep understanding of the analytical model; while observation-level interaction offers familiar interface embedded in the domain semantics, but changes made by the user may be incorrectly translated into model updates.…”
Section: At Which Stage Is the Interaction Happeningmentioning
confidence: 99%
“…‘magnets’ representing keywords), not data itself. On the other hand, tools such as ForceSPIRE [EFN12], Dis‐function [BLBC12], Andromeda [SH] and StarSPIRE [BNH14] focus on using human cognition to steer the underlying computations by directly manipulating the spatializations, giving users the chance to interact with data points and translate this feedback through a dimension‐reduction algorithm to a new view reflecting the user's interaction. This helps provide an intuitive space for strengthening insight creation and data understanding.…”
Section: Related Workmentioning
confidence: 99%
“…To study OLI, we designed and developed an interactive interface, Andromeda (Figure 1), that visualizes high-dimensional data using WMDS [8]. Andromeda's object view (Figure 1a) visualizes the WMDS projection and the parameter view ( Figure 1b) displays the weights as horizontal lines.…”
Section: Object-level Interactionmentioning
confidence: 99%
“…Previous research involving a controlled user study found the interactions within Andromeda allowed users to perform successful data analyses [8]. OLI and parametric interaction provide the user with two analysis angles: object-centric and dimension-centric.…”
Section: Object-level Interactionmentioning
confidence: 99%